Outdoor Play and Learning in Elementary Schools: A Critical Participatory Action Research Project - Zeni, Megan; Schnellert, Leyton; Brussoni, Mariana (The Canadian Journal of Action Research)

(untitled) (Canadian Association of Action Research in Education, 2024)
In this study, we enacted critical participatory action research (CPAR) within an online community of practice (CoP). The CoP was designed to build a community of outdoor play and learning (OPAL) practitioners. This paper describes how a cohort (n=18) of experienced Kindergarten to grade eight (K-8) teachers from across British Columbia shared their OPAL experiences and practice and the collective action taken. Regularly scheduled meetings over a six-month period resulted in dialogue that identified the need for quality resources that were accessible for all teachers. The concept of a website, developed for teachers by teachers experienced with OPAL, was initiated within the CPAR process. This article describes findings related to participation in a CPAR CoP, and the process of deciding upon and enacting shared action to support OPAL elementary school teachers.